Respuesta :

xplanation:

Step 1. e are given the following zeros of a polynomial function.

- 1 with a multiplicity of two, which means that is a zero two times:

[tex]\begin{gathered} x_1=1 \\ x_2=1 \end{gathered}[/tex]

and the other two zeros are:

[tex]\begin{gathered} x_3=2+\sqrt{2} \\ x_4=2-\sqrt{2} \end{gathered}[/tex]

And we need to find the equation that has these four zeros.

tep 2. 2R

[tex]f(x)=(x-x_1)(x-x_2)(x-x_3)(x-x_4)[/tex]

tep 3. S

[tex]f(x)=(x-1)(x-1)(x-(2+\sqrt{2}))(x-(2-\sqrt{2}))[/tex]

tep 4. S

[tex]f(x)=(x-1)(x-1)(x-2-\sqrt{2})(x-2+\sqrt{2})[/tex]

tep 5. T

[tex]f(x)=(x^2-2x+1)(x-2-\sqrt{2})(x-2+\sqrt{2})[/tex]

Then, let's multiply the second and third parentheses:

[tex]f(x)=(x^2-2x+1)(x^2-2x+x\sqrt{2}-2x+4-2\sqrt{2}-x\sqrt{2}+2\sqrt{2}-2)[/tex]

Multiple terms cancel and the result is:

[tex]f(x)=(x^2-2x+1)(x^2-4x+2)[/tex]

tep 6. TT

[tex]f(x)=x^4-4x^3+2x^2-2x^3+8x^2-4x+x^2-4x+2[/tex]

Combining like terms:

[tex]f(x)=x^4-6x^3+11x^2-8x+2[/tex]

This is shown in option D.

Answer:

D

[tex]f(x)=x^4-6x^3+11x^2-8x+2[/tex]